Determinant of ARI Incident in Toddlers in The Working Area of Tomia Health Center Wakatobi Regency - Sitti Marya Ulva; Finasti (Miracle Journal of Public Health, 2022)
Infections in the upper respiratory tract are the cause of under-five mortality and are also a crucial health problem in Indonesia, the main cause in the Tomia Health Center area which every year has increased, namely in 2018 the prevalence of toddler ARI cases by 9,4%, in 2019 by 12,8% while in 2020 increased to 17,0%. The motivation behind the review is to discover the determinant of ARI events in toddlers in the Working Area of Tomia Health Center Wakatobi Regency. This kind of examination is an insightful study with a Cross-Sectional Study plan. The review populace was all moms who had toddlers in the Tomia Health Center Work Area as numerous as 705 people with a sample number of 88 toddlers taken proportionally random sampling. The analysis method uses the Chi-Square test. The results of the study with Chi-Square test showed that the ventilation variables of the house obtained values (X2calculated= 27.381 and = 0.581), occupancy density (X2count= 27.929 and = 0.586) air pollution in the house (X2count= 22,863 and = 0.533) and floor type (X2count= 19.939 and = 0.499). The conclusion pf this study that there is a relationship between home ventilation, occupancy density, air contamination in the house and the kind of floor with the rate of ARI in toddlers in the Tomia Health Center Work Area. It is recommended to the Tomia Health Center to further improve counselling related to the importance of a health-qualified home environment.